Hospitalitas Menurut Amos Yong dan Falsafah Hidup Orang Basudara untuk Dialog Interreligius - Sopacuaperu, Eklepinus Jefry (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2019)
This article aims to explore hospitality as the basic character needed in developing interreligious dialogues. The underlying idea is that every religion has its particular characteristics of hospitality that can be valuable to start an effective dialogue. The author discerns the local wisdom phrased as hidup orang basudara as one of the chracteristics of the Moluccan hospitality that can be used to develop interreligious dialogue in Molucca, Indonesia. By drawing insights from the derriderian concept of “true hospitality” that surpasses ‘friendship’, hospitality model is offered as a better alternative in the praxis of building interreligious dialogue. This model is also considered more relevant to the people of Molucca, especially among the Christians and the Muslims, during the post-conflict period. The concept of hospitality is in line with some of the Moluccan local wisdoms that are explored in this article as well. In order to embark on the journey of reconciliation, people are invited to go beyond friendship, that is, towards living together as brothers and sisters.